C# 2.0 : - Champlain, Michel De (Elsevier, 2005)
C# 2.0: A Practical Guide provides an amazing breadth of information in a compact and efficient format, with clear and concise writing and useful code examples. It cuts right to the core of what you need to know, covering every aspect of the C# language, an introduction to the .NET API, and an overview of pertinent object-oriented concepts. This book tops my recommendation list for any developer learning C#.